Fire Hazard Analysis on Different Fire Source Locations in Multi-Segment Converging Tunnel with Structural Beams - Lixin Wei; Honghui Tang; Jiaming Zhao; Shiyi Chen; Yiqiang Xie; Shilin Feng; Zhisheng Xu; Zihan Yu (Fire, 2023)
To investigate the fire risk in a complex tunnel with varying cross-sections, sloped structures, and dense upper cover beams, this study considered four fire source positions: the immersed tube section, confluence section, highway auxiliary road section, and four-lane sections of the main line. It also considered four beam spacings: 1 m, 1.8 m, 3.6 m, and 7.2 m. The Fire Dynamics Simulation Software FDS was utilized to create a comprehensive tunnel model. The analysis focused on temperature and visibility changes at a 2 m height under a 20 MW fire condition for different fire source positions. These changes were then compared with critical danger values to assess the safety of evacuating personnel within the tunnel. Subsequently, this study proposed corresponding emergency rescue strategies. The findings indicated that when the beam grid spacing exceeded 3.6 m, the upper dense beam gap showed a robust smoke storage capacity, leading to a reduced distance of high-temperature smoke spread. However, this increased smoke storage disrupted the stability of the smoke layer, resulting in a heightened smoke thickness. The location of the ventilation vent at the entrance of the immersed tunnel section caused a non-uniform ventilation flow under the girder, deflecting the smoke front towards the unventilated side and decreasing visibility in the road auxiliary area. In comparison to scenarios without a beam lattice, the presence of a beam lattice in the tunnel amplified fire hazards. When the beam lattice spacing was 3.6 m or greater, the extent of the hazardous environment, which is unfavorable for personnel evacuation, expanded. With the exception of the scenario where the fire source was located in the highway auxiliary roadway, all other conditions surpassed 150 m, which is roughly one-third of the tunnel length. Consequently, more targeted strategies are necessary for effective evacuation and rescue efforts.